Pengujian Kemurnian Genetik Benih Padi Galur F3 (Pandanwangi x PTB33) Terseleksi Menggunakan Marka Molekuler Simple Sequence Repeats (SSR) - Syindy Raffini Nasihin; Wieny H. Rizky; Nono Carsono (Fakultas Pertanian Universitas Padjadjaran, 2015)
ABSTRACTSeed Purity Testing of F3 Progeny of Rice Lines Derived from a Cross between Pandanwangi x PTB-33 Estimated by Simple Sequence Repeat MarkersSeeds with high purity is required to produce maximum crop yield. Genetic purity of selected F3rice seed progenies derived from a cross between Pandanwangi x PTB33 was estimated by SSR(simple sequence repeats) molecular markers. Objective of current experiment was to obtain riceseed with high genetic purity (100%) in terms of homogeneity of alleles. The experiment wasconducted at Laboratory of Plant Analysis and Biotechnology, meanwhile field experiment wasperformed at Ciparanje Experimental Station, Faculty of Agriculture, Universitas Padjadjaran.Based on primer designed by Bradbury (aromatic trait) and primers RM589 and RM586 (supposedto correlate with brown planthopper resistance gene), seeds of F3 selected had 100% geneticpurity. SSR markers applied for each offspring were able to demonstrate the purity of the seed.Genotypes with 100% genetic purity can be continued for propagating their seeds.Keywords: F3, seed purity, seed rice, SSR markersABSTRAKBenih dengan kemurnian genetik tinggi sangat diperlukan untuk produksi tanaman yangmaksimal. Kemurnian genetik padi generasi F3 hasil persilangan Pandanwangi x PTB-33 diestimasidengan menggunakan marka molekuler SSR. Percobaan ini bertujuan untuk mendapatkan generasiF3 yang memiliki kemurnian genetik 100%. Penelitian dilaksanakan di Kebun PercobaanCiparanje, Fakultas Pertanian Universitas Padjadjaran dan Laboratorium Analisis dan BioteknologiTanaman. Hasil analisis menggunakan primer Bradbury menunjukkan 100% benih murniberdasarkan karakter aromatik, begitupun berdasarkan karakter ketahanan terhadap wereng(primer RM589 dan RM586) menunjukkan 100% benih murni. Marka molekuler SSR yangdigunakan untuk verifikasi kemurnian mampu menunjukkan kemurnian genetik benih padi yangtinggi. Genotip PP dapat dilanjutkan untuk pengujian dan atau perbanyakan benih sumber.Kata kunci: benih padi, F3, marka SSR, uji kemurnian genetik